Religious Conflicts: Opportunity Structures, Group Dynamics, and Framing - Lindgren, Tomas (Pascasarjana IAIN Pontianak, 2018)
Explanations of violent religious conflicts usually focus on preconditions, facilitator causes or precipitating events at micro, meso or macro levels of analysis. As social psychology is the scientific study of the ways in which thoughts, feelings, perceptions, motives, and behaviors are influenced by interactions and transactions between groups and individuals, it can increase our understanding of the dynamics of religious conflicts at micro and meso levels. In this paper, I illustrate this point with a discussion of the utility of social movement theory for understanding the dynamics of religious conflicts. Social movement theory locates religious conflicts within broader contexts and complex processes by focusing on the interplay between micro and meso factors and the ways in which people perceive macro factors. Given certain conditions, religion can and often do contribute to collective violence. Religion is rarely, if ever, the main cause of intergroup conflicts, but is often used as an instrument for the mobilization of human and non-human resources. Appeal to religion may help conflicting parties overcome the collective action problem associated with intergroup conflicts. This does not necessarily mean that religious conflicts have unique characteristics or a logic of their own that sets them apart from other types of intergroup conflicts.